2017
DOI: 10.1016/j.pepi.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Seismic arrival enhancement through the use of noise whitening

Abstract: A constant feature in seismic data, noise is particularly troublesome for passive seismic monitoring where noise commonly masks microseismic events. We propose a statistics-driven noise suppression technique that whitens the noise through the calculation and removal of the noise's covariance. Noise whitening is shown to reduce the noise energy by a factor of 3.5 resulting in microseismic events being observed and imaged at lower signal to noise ratios than originally possible -whilst having negligible effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Whereas, stacking procedures typically require multiple nearby stations and are therefore not applicable for single station or sparse array applications, ruling out their use for a significant portion of hazard monitoring scenarios. Alternative approaches could be to include a noise suppression procedure prior to detection, however that would introduce an unwanted additional computational cost and due to the varying nature of noise signals it would be difficult to determine an automated noise suppression algorithm which is optimal [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, stacking procedures typically require multiple nearby stations and are therefore not applicable for single station or sparse array applications, ruling out their use for a significant portion of hazard monitoring scenarios. Alternative approaches could be to include a noise suppression procedure prior to detection, however that would introduce an unwanted additional computational cost and due to the varying nature of noise signals it would be difficult to determine an automated noise suppression algorithm which is optimal [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the topic has gained more attention and a couple of specialized techniques for noise suppression in microseismic monitoring have been developed. The suggested methods include downweighting or removal of stations based on their noise level (Trojanowski 2019;Alexandrov et al 2020), coherent noise removal using multichannel convolution filters (Trojanowski 2019), curvlet-based noise filtering (Trojanowski 2019) and statistical noise whitening (Birnie et al 2017). These methods look promising but it is important to consider that filtering can potentially damage the signal.…”
Section: The Importance Of Pre-processingmentioning
confidence: 99%
“…Chambers et al 2010;Pesicek et al 2014;Zeng et al 2014). Recently, new noise suppression techniques have been suggested that are specially designed for microseismic monitoring (Birnie et al 2017;Trojanowski 2019;Alexandrov et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Noise is particularly troublesome for microseismic monitoring where the signal often arises from a low magnitude event, and is therefore, hidden below the noise (Maxwell, 2014), which can result in errors and artefacts in detection and imaging procedures (Bardainne et al, 2009). As such, large efforts are made to reduce the noise from data collection (e.g., Maxwell, 2010;Auger et al, 2013;Schilke et al, 2014) to data processing (e.g., Eisner et al, 2008;Mousavi and Langston, 2016;Birnie et al, 2017), and to ensure monitoring algorithms are adequately tested under realistic noise conditions (Birnie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%